Recurrent Kawasaki disease with polyserositis and pulmonary lesions in a 5-year-old boy: a case report - Weng, Jiahui; Wen, Yang; Li, Yiyuan (Frontiers in Pediatrics, 2025)
BackgroundKawasaki disease (KD) is associated with coronary artery alterations, and recurrence of the disease is relatively rare. We here report a case of recurrent KD complicated by polyserositis and pulmonary lesions in a young male patient.Case presentationA 5 year old male experienced a recurrence of KD complicated by polyserositis and pulmonary lesions, with concurrent Shigella bogdii infection. The simultaneous occurrence of these complications is exceptionally uncommon. An early diagnosis was established, and systemic immunosuppressive therapy was promptly initiated. The therapeutic intervention proved to be effective, leading to a complete resolution of the condition.ConclusionKD may induce polyserositis, heart failure, and pulmonary lesions, making early diagnosis and immediate treatment crucial for prognostic enhancement.